Return to Sports After Anterior Cruciate Ligament Reconstruction: Validity and Reliability of the SPORTS Score at 6 and 12 Months. Issue 6 (8th June 2022) - Bley, Jordan A.; Master, Hiral; Huston, Laura J.; Block, Shannon; Pennings, Jacquelyn S.; Coronado, Rogelio A.; Cox, Charles L.; Sullivan, Jaron P.; Dale, Kevin M.; Saluan, Paul M.; Spindler, Kurt P.; Archer, Kristin R.
Background: The Subjective Patient Outcome for Return to Sports (SPORTS) score is a single-item scale that measures athletes' ability to return to their preinjury sport based on effort and performance. Purpose/Hypothesis: The purpose of this study was to examine the psychometric properties of the SPORTS score and a modified score within the first year after anterior cruciate ligament reconstruction (ACLR). The modified version replaced "same sport" with "any sport" in the answer choices. It was hypothesized that both versions of the SPORTS score would have acceptable floor and ceiling effects and internal responsiveness, moderate convergent validity, and excellent test-retest reliability. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: Patients were recruited preoperatively from 2 academic medical centers. The authors collected responses to the 1-item SPORTS scores at 6 and 12 months after ACLR and the Tegner activity scale, Lysholm knee score, Knee injury and Osteoarthritis Outcome Score (KOOS)–sport/recreation subscale, and Marx activity rating scale preoperatively and 6 and 12 months after ACLR. Ceiling and floor effects and responsiveness were assessed using descriptive statistics and cross-tabulations, respectively, at both follow-up time points. Spearman correlations and intraclass correlation coefficients were used to examine convergent validity and test-retest reliability, respectively. Results: Follow-up rates at 6 and 12 months were 100% and 99%, respectively. Test-retest follow-up was 77%. Floor effects for the SPORTS scores were not observed, while ceiling effects at 12 months ranged from 38% to 40%. Cross-tabulation of the SPORTS scores showed that 64% to 66% of patients reported a change in their score from 6 to 12 months, with significant differences noted between the proportions that improved versus worsened for return to any sport. Convergent validity was observed at 6 and 12 months via moderate correlations with the Tegner, Lysholm, KOOS–sport/recreation, and Marx scores ( r = 0.31 to 0.47). Fair to good test-retest reliability (intraclass correlation coefficient, 0.58 and 0.60) was found at 12 months after ACLR. Conclusion: The SPORTS score appears to be a reliable, responsive, and valid 1-item scale that can be used during the first year after ACLR. No differences in psychometric properties were found between the SPORTS score and the modified version.